2016
DOI: 10.1007/s12325-016-0351-4
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Triptorelin: Current Thinking on Androgen Deprivation Therapy for Prostate Cancer

Abstract: Androgen deprivation therapy (ADT) is the mainstay palliative treatment for men with locally advanced and metastatic prostate cancer, and aims to reduce testosterone to levels obtained by surgical castration. Use of gonadotropin-releasing hormone (GnRH) agonists predominates among the ADT options. The GnRH agonist, triptorelin is a first-line hormonal therapy that has demonstrated efficacy and safety in clinical trials of patients with locally advanced non-metastatic or metastatic disease. Sustained-release 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 73 publications
0
32
0
5
Order By: Relevance
“…The main objective of any ADT is to rapidly suppress testosterone to castrate levels as elevated testosterone levels are associated with an increased risk of progression of prostate cancer [ 16 ]. Importantly, serum testosterone levels as low as 0.25 ng/mL indicate a good prognosis in patients with prostate cancer receiving ADT [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of any ADT is to rapidly suppress testosterone to castrate levels as elevated testosterone levels are associated with an increased risk of progression of prostate cancer [ 16 ]. Importantly, serum testosterone levels as low as 0.25 ng/mL indicate a good prognosis in patients with prostate cancer receiving ADT [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the half-life of GnRH-I is only 2-5 minutes before cleavage by serum proteases; GnRH agonists, including triptorelin, can extend its half-life and increase binding to receptors [14]. In the treatment of prostate cancer, triptorelin is a first-line hormone therapy and can be efficacious and safe for patients with advanced prostate cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown a reduction in serum testosterone levels below the castration level [45,46].…”
Section: Lhrh Agonistsmentioning
confidence: 99%
“…Overstimulation of LH release desensitizes and down regulates pituitary receptors for LHRH. Goserelin and triptorelin were accepted in the early 2000s [46,50]. LHRH agonists have shown similar effectiveness to surgical castration procedures in survival context.…”
Section: Abiraterone Acetatementioning
confidence: 99%